2015
DOI: 10.1016/j.jssdds.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Madura foot: Report of a eumycetoma Moroccan case

Abstract: Madura foot is a chronic infectious disease, caused by bacterial actinomycetes or by fungi. Mycetoma is endemic in tropical and subtropical areas, where it is a real public health issue. It is a rare and neglected disease in our country. The diagnosis is made by clinical picture, direct microscopic examination and histological study.The best therapeutic choice is surgical removal of the lesion, followed by medical treatment. An earlier diagnosis and treatment can elicit good results. We report a case of eumyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Grains can be black in color if caused by M. mycetomatis, Trematosphaeria grisea, Falciformispora senegalensis (formerly Leptosphaeria senegalensis), Falciformispora thompkinsii, Exophiala jeanselmei, Pyrenochaeta romeroi, Curvularia lunata and Phialophora verrucosa, among other agents; or white if caused by Scedosporium apiospermum, Aspergillus nidulans, Aspergillus flavus, Fusarium sp., Acremonium sp., Nostestudina rosatti and Microsporum audouinii, among the most common 6 . Actinomycetomas can produce grains, usually of red or yellow color, but they can produce white grains as well, and microbiological is therefore essential to differentiate between eumycetoma and actinomycetoma 28 . To verify the presence of the causative agent, direct examination should be carried out, as well as purulent exudate sampling for culture.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Grains can be black in color if caused by M. mycetomatis, Trematosphaeria grisea, Falciformispora senegalensis (formerly Leptosphaeria senegalensis), Falciformispora thompkinsii, Exophiala jeanselmei, Pyrenochaeta romeroi, Curvularia lunata and Phialophora verrucosa, among other agents; or white if caused by Scedosporium apiospermum, Aspergillus nidulans, Aspergillus flavus, Fusarium sp., Acremonium sp., Nostestudina rosatti and Microsporum audouinii, among the most common 6 . Actinomycetomas can produce grains, usually of red or yellow color, but they can produce white grains as well, and microbiological is therefore essential to differentiate between eumycetoma and actinomycetoma 28 . To verify the presence of the causative agent, direct examination should be carried out, as well as purulent exudate sampling for culture.…”
Section: Diagnosismentioning
confidence: 99%
“…One recent phylogenetic analysis demonstrated that M. mycetomatis and M. grisea belong to different orders; currently, the Madurella genus is comprised by M. mycetomatis, M. pseudomycetomatis, M. tropica and M. fahalii, which belong to the Sordiales order, whereas M. grisea is member of the Pleosporales and went on to be denominated Trematosphaeria grisea 29,30,52,53 . In addition, four CBS sterile mycelium dematiaceous strains obtained from patients with mycetoma, originally identified by traditional methods as M. mycetomatis, showed significant differences in the ITS region, thus being demonstrated that they belong to different species; none of these strains was native to Africa 28 . Subsequently, inclusion of the Madurella genus in the Chaetomiaceae family was demonstrated; member of this family are commonly found in dung and manure, which drove to conclude that the manure present in endemic areas can be a niche for Madurella and play an essential role in eumycetoma acquisition 54 .…”
Section: Advances In Molecular Identification and Phylogenymentioning
confidence: 99%
“…Los granos pueden ser negros si son causados por M. mycetomatis, Trematosphaeria grisea, Falciformispora senegalensis (antes Leptosphaeria senegalensis), Falciformispora thompkinsii, Exophiala jeanselmei, Pyrenochaeta romeroi, Curvularia lunata y Phialophora verrucosa, entre otros agentes; o blancos si son ocasionados por Scedosporium apiospermum, Aspergillus nidulans, Aspergillus flavus, Fusarium sp., Acremonium sp., Nostestudina rosatti y Microsporum audouinii, entre los más frecuentes 6 . Los actinomicetomas pueden producir granos, comúnmente de color rojo o amarillo, pero también pueden producir granos blancos, por lo que el diagnóstico microbiológico es fundamental para diferenciar entre eumicetoma y actinomicetoma 28 . Con objeto de comprobar la presencia del agente causal debe realizarse un examen directo, así como la toma de exudado purulento para cultivo.…”
Section: Diagnósticounclassified
“…Un análisis filogenético reciente demostró que M. mycetomatis y M. grisea pertenecen a diferentes órdenes; en la actualidad, el género Madurella se encuentra constituido por M. mycetomatis, M. pseudomycetomatis, M. tropica y M. fahalii, que pertenecen al orden Sordiales, mientras que M. grisea es miembro de los Pleosporales y pasó a denominarse Trematosphaeria grisea 29,30,52,53 . Además, cuatro cepas dematiáceas de micelio estéril CBS obtenidas de pacientes con micetoma, originalmente identificadas por métodos tradicionales como M. mycetomatis, mostraron diferencias significativas en la región ITS, demostrándose que representan especies diferentes; ninguna de estas cepas era originaria de África 28 . Posteriormente se demostró la inclusión del género Madurella en la familia Chaetomiaceae; miembros de esta familia se encuentran frecuentemente en el estiércol y en el abono, por lo que se concluyó que el estiércol presente en las áreas endémicas puede ser un nicho para Madurella y desempeñar un papel primordial en la adquisición del eumicetoma 54 .…”
Section: Avances En Identificación Y Filogenia Molecularunclassified